2018
DOI: 10.18203/2349-3291.ijcp20181036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of picky eating behavior and its impact on growth in preschool children

Abstract: Background: Almost two-thirds of parents report one or more problems with their children’s eating. Although knowledge of the health-related outcomes of picky eating is limited due to a lack of longitudinal studies, research suggests that picky eating is associated with nutrient deficiency, underweight, behavioral problems and symptoms of anxiety and depression. Aim of present study was to assess the Parental perception and maternal strategies in solving feeding difficulties in relation with parenting style.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…In this study, we found that 67.5% of children aged 4–7 were picky eaters, which is slightly higher than previous studies of Asian children. This seems to indicate that the prevalence of picky eaters increases with age, which is supported by some studies [ 52 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we found that 67.5% of children aged 4–7 were picky eaters, which is slightly higher than previous studies of Asian children. This seems to indicate that the prevalence of picky eaters increases with age, which is supported by some studies [ 52 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 76%
“…Picky eating is a complex behavior commonly seen in children which can significantly affect their growth, cause impaired cognition and poor immunity. The findings of the cross-sectional study from Telangana on 1652 parents of preschool children in the age group of 1-6 years revealed that 58.9% of the children were picky eaters [16].…”
Section: Picky Eatingmentioning
confidence: 98%
“…A poor eating self-regulation in children has been associated with higher body weight ( Hughes and Frazier-Wood, 2016 ). Picky eating is common in preschool children, which leads to parental anxiety and family conflicts ( Kumar et al, 2018 ). Authoritative parenting has a positive correlation with non-picky eating in their toddler, suggesting that this parent feeding behavior could overcome the feeding difficulties ( Podlesak et al, 2017 ).…”
Section: Obesogenic Environmentmentioning
confidence: 99%